Choosing Healthy Eating for Infant Health (CHErIsH) study: protocol for a feasibility study. Issue 8 (22nd August 2019) - Matvienko-Sikar, Karen; Toomey, Elaine; Queally, Michelle; Flannery, Caragh; O Neill, Kate; Dinan, Ted G; Doherty, Edel; Harrington, Janas M; Hayes, Catherine; Heary, Caroline; Hennessy, Marita; Kelly, Colette; et al.
Abstract : Introduction: Childhood obesity is a public health challenge. There is evidence for associations between parents' feeding behaviours and childhood obesity risk. Primary care provides a unique opportunity for delivery of infant feeding interventions for childhood obesity prevention. Implementation strategies are needed to support infant feeding intervention delivery. The Choosing Healthy Eating for Infant Health (CHErIsH) intervention is a complex infant feeding intervention delivered at infant vaccination visits, alongside a healthcare professional (HCP)-level implementation strategy to support delivery. Methods and analysis: This protocol provides a description of a non-randomised feasibility study of an infant feeding intervention and implementation strategy, with an embedded process evaluation and economic evaluation. Intervention participants will be parents of infants aged ≤6 weeks at recruitment, attending a participating HCP in a primary care practice. The intervention will be delivered at the infant's 2, 4, 6, 12 and 13 month vaccination visits and involves brief verbal infant feeding messages and additional resources, including a leaflet, magnet, infant bib and sign-posting to an information website. The implementation strategy encompasses a local opinion leader, HCP training delivered prior to intervention delivery, electronic delivery prompts and additional resources, including a training manual, poster and support from the research team. An embedded mixed-methods process evaluation will examine the acceptability and feasibility of the intervention, the implementation strategy and study processes including data collection. Qualitative interviews will explore parent and HCP experiences and perspectives of delivery and receipt of the intervention and implementation strategy. Self-report surveys will examine fidelity of delivery and receipt, and acceptability, suitability and comprehensiveness of the intervention, implementation strategy and study processes. Data from electronic delivery prompts will also be collected to examine implementation of the intervention. A cost–outcome description will be conducted to measure costs of the intervention and the implementation strategy. Ethics and dissemination: This study received approval from the Clinical Research Ethics Committee of the Cork Teaching Hospitals. Study findings will be disseminated via peer-reviewed publications and conference presentations.